Impact Analysis of Pandemic on Nigeria’s Stock Market Performance - Akinbobola, T. O.; Awosoga, O. A.; Babalola, C. P.; Okunade, S. O.; Agumadu, M. A.; Shuaib, F. L. (Research in Applied Economics, 2024)
We empirically conducted a distinct analysis of the efficiency of the stock market before and during the Covid-19 pandemic in Nigeria as well as the impact of the Covid-19 pandemic on several indicators of stock market performance. Data were collected on stock variables on monthly basis for the pre-Covid-19 era (2018M02 to 2020M01) and Covid-19 pandemic era (2020M02 to 2022M01) from the Central Bank of Nigeria Statistical Bulletin, while data on the numbers of daily new confirmed cases (New cases and deaths) as well as the government response stringency index on COVID-19 pandemic were obtained from Our World in Data (OWID). We leveraged numerous advantages of the Data Envelopment Analysis (DEA) to estimate stock market efficiency before and during the Covid-19 pandemic for the purpose of comparison. Also, we employed the Autoregressive Distributed Lag Mixed Data Sampling (ADL-MIDAS) approach to conduct the impact analysis of the Covid-19 pandemic on stock market performance. We found that, in terms of efficiency, the stock market was more efficient during the Covid-19 pandemic than in the pre-Covid-19 era, being the only active market among other financial markets especially when several restrictions and total lockdown were imposed. In terms of returns and volatility, the study concluded that the Covid-19 pandemic did not significantly influence Nigeria’s stock market performance negatively. However, the government stringency measures had a significant positive impact on the stock market return in Nigeria. Our findings are instructive to policymaking and financial regulation.